Mathematical modeling of age differences in hierarchical navigation systems - Zaphiris, Panayiotis; Ellis, R. Darin (My University, 2000)
The mathematical modeling of age differences in hierarchical navigation systems was studied. A modification to an existing mathematical model for depth-breath trade-off of menu selection to account for age related differences was presented. The depth-breadth trade-off was extensively examined, both empirically and analytically. Contour plots of various combinations of breadth and depth were plotted for two age groups (25 and 70 years of age).
Keywords: Aging; Cognitive modeling; Menu selection; Navigation